Gluten-Free Diet Does Not Appear to Induce Endoscopic Remission of Eosinophilic Esophagitis in Children with Coexistent Celiac Disease. (2012) - Abraham, Joseph R; Persad, Rabin; Turner, Justine M; Huynh, Hien Q
Abstract : BACKGROUND: Celiac disease and eosinophilic esophagitis are usually considered to be separate gastrointestinal diseases; however, it appears that they may coexist more often than would be expected. It is unknown whether eosinophilic esophagitis in patients with celiac disease responds to a gluten-free diet. OBJEVTIVES: To examine the clinical, endoscopic and histological features of children with both conditions to evaluate whether eosinophilic esophagitis responds to a gluten-free diet. METHODS: From January 1, 2009, to June 30, 2011, the medical records of children <18 years of age diagnosed with eosinophilic esophagitis and/or celiac disease were reviewed. Patients with clinical, endoscopic and histological diagnoses of both diseases were identified and included. These findings were analyzed, as were laboratory results, treatment and follow-up. RESULTS: During the study period, there were 206 celiac disease patients, 86 eosinophilic esophagitis patients and nine (4.4% of total celiac) patients with both diagnoses. Gluten-free diet was the primary treatment for both conditions in seven of nine (78%) cases. In six of these seven (86%) patients, no endoscopic or histological improvement of eosinophilic esophagitis was observed, while in one patient, histological remission of esophageal eosinophilia occurred while on a gluten-free diet. CONCLUSION: The prevalence of eosinophilic esophagitis in patients with celiac disease was 4.4%, confirming a higher than expected prevalence of eosinophilic esophagitis compared with the general population. In patients with celiac disease, a gluten-free diet did not appear to induce remission of coexistent endoscopic and histological features of eosinophilic esophagitis.